Green magnetic composite sheet from durian shell and nano magnetite particles - Mustaq, Mohd Khairul Shahril; Munawar, Rose Farahiyan; Mohamed, Muhd Hafez; Arif, Afraha Baiti; Mohamad, Noraiham; Ab Maulod, Hairul Effendy; Abd Manaf, Mohd Edeerozey; ABD RAZAK , JEEFFERIE (Trans Tech Publications, 2015)
Abstract. Biomass-derived materials such as kenaf pulp and wood chips are a perfect candidate to produce magnetic paper. Furthermore, by using biomass waste, such as paddy straw, sugarcane, bagasse and durian shell, the cost of producing magnetic paper can be further reduced while giving added value to the waste. This paper investigates the potential of producing magnetic sheet from durian shell. Initially, durian shells were dried before undergoing the pulping process. The resulted sheet was then combined with magnetic particles, the nano magnetite using either lumen loading or in-situ co-precipitation to produce a magnetic composite sheet. After being loaded with magnetic particles, the composite sheets were tested in terms of the homogeneity of the magnetic particles in the samples, degree of loading of the magnetic particles and the magnetic properties of the samples. Results obtained show a great success in producing the magnetic sheet from durian shell waste and nano magnetite particles. It was also found that the lumen loading method gives better magnetic properties compared to the in-situ co-precipitation method.